Chemical process equipment selection and design - Couper, James R. (Butterworth-Heinemann, 2010)
Chemical Process Equipment is a results-oriented reference for engineers who specify, design, maintain or run chemical and process plant. This book delivers information on the selection, sizing and operation of process equipment in a format that enables quick and accurate decision making on standard process and equipment choices, saving time, improving productivity, building understanding. Coverage emphasizes common real-world equipment design, rather than experimental or esoteric, and focuses on maximizing performance. Legacy reference for chemical and related engineers who work with vendors to design, specify and make final equipment selection decisions. Copious examples of successful applications, with supporting schematics and data to illustrate the functioning and performance of equipment. Provides equipment rating forms and manufacturers' data, worked examples, valuable shortcut methods, and rules of thumb to demonstrate and support the design process. Heavily illustrated with line drawings and schematics to aid understanding, as well as graphs and tables to illustrate performance data.
Keywords: Chemical processes -- Equipment and supplies.; Chemical engineering -- Equipment and supplies.; elektronické knihy; electronic books